Treatment of Class III Malocclusion with Open Bite and Macroglossia Using an Anterior Loop: Perawatan Maloklusi Klas III dengan Gigitan Terbuka dan Makroglosia Menggunakan Loop Anterior - Lila Muntadir (Academia Open, 2024)
General Background: Class III malocclusion is a prevalent dental anomaly characterized by the anterior positioning of the mandible relative to the maxilla, posing functional and aesthetic challenges. Specific Background: This condition may present with additional complexities such as dental crowding, open bite, and macroglossia, complicating the orthodontic treatment approach. Knowledge Gap: While conventional treatment modalities include orthognathic surgery and growth modification, there is limited documentation on the efficacy of orthodontic camouflage in non-surgical settings, particularly in adults with completed growth. Aims: This study aims to evaluate the effectiveness of orthodontic camouflage using anterior stainless steel loops in managing dentoskeletal Class III malocclusion accompanied by anterior open bite and macroglossia, without premolar extraction. Results: Over a 7-month treatment period, significant corrections in overjet, overbite, and molar relationship were achieved, demonstrating the potential of this approach as a non-surgical alternative. Novelty: This research introduces a modified technique involving stainless steel wire with specific loop placements, contributing to the orthodontic management strategies for complex Class III cases. Implications: The findings support the broader application of camouflage techniques in orthodontic practice, offering a viable option for patients opting out of surgery and highlight the need for further studies to optimize and validate such approaches.Highlights: Efficiency of Camouflage: Shows how orthodontic camouflage can effectively treat complex Class III malocclusion without surgery. Novel Technique: Introduces a new method using stainless steel loops in wires to enhance treatment outcomes. Clinical Implications: Expands non-surgical treatment options in orthodontics, offering viable alternatives to surgery. Keywords: Class III Malocclusion, Orthodontic Camouflage, Open Bite, Macroglossia